Do Omega-3 fatty acids prevent atrial fibrillation after open heart surgery? A meta-analysis of randomized controlled trials (Clinics, 2011)
OBJECTIVES: N-3 polyunsaturated fatty acids have been proposed as a novel treatment for preventing postoperative atrial fibrillation due to their potential anti-inflammatory and anti-arrhythmic effects. However, randomized studies have yielded conflicting results. The objective of this study is to review randomized trials of N-3 polyunsaturated fatty acid use for postoperative atrial fibrillation. METHODS: Using the CENTRAL, PUBMED, EMBASE, and LILACS databases, a literature search was conducted to identify all of the studies in human subjects that reported the effects of N-3 polyunsaturated fatty acids on the prevention of postoperative atrial fibrillation in cardiac surgery patients. The final search was performed on January 30, 2011. There was no language restriction, and the search strategy only involved terms for N-3 polyunsaturated fatty acids (or fish oil), atrial fibrillation, and cardiac surgery. To be included, the studies had to be randomized (open or blinded), and the enrolled patients had to be >;18 years of age. RESULTS: Four randomized studies (three double-blind, one open-label) that enrolled 538 patients were identified. The patients were predominantly male, the mean age was 62.3 years, and most of the patients exhibited a normal left atrial size and ejection fraction. N-3 polyunsaturated fatty acid use was not associated with a reduction in postoperative atrial fibrillation. Similar results were observed when the open-label study was excluded. CONCLUSIONS: There is insufficient evidence to suggest that treatment with N-3 polyunsaturated fatty acids reduces postoperative atrial fibrillation. Therefore, their routine use in patients undergoing cardiac surgery is not recommended.